Experience of Studying Innovative Behavior of Youth in Russia (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
Transformations in society need to raise the level of their economic consciousness. The problem is that the level of innovation remains low. The article presents the description of the innovative economic behaviour study. A survey was done on students from different courses. The experiment was aimed at studying the group interaction factors in the formation of innovative behaviour. We proceeded from the proposition that innovativeness is a derivative of individual creativity and external factors, in particular, the factor of group interaction. We assume that factors of group interaction are more important for the development of innovative economic behavior. The case study have a several stages. First, the level of individual creativity and innovativeness was studied. Then the subjects received a task during the week. The results showed that the level of individual creativity is not a sufficient condition for the manifestation of innovative behaviour. Group factors play an important role in it as well. More importantly for team work is intra-group cognitive and social processes. In addition, the results of the case study, suggest that innovation is a skill that can be developed.